The yeast Sgs1 helicase is differentially required for genomic and ribosomal DNA replication - Versini, Gwennaelle (Oxford University Press, 2003)
The members of the RecQ family of DNA helicases play conserved roles in the preservation of genome integrity. RecQ helicases are implicated in Bloom and Werner syndromes, which are associated with genomic instability and predisposition to cancers. The human BLM and WRN helicases are required for normal S phase progression. In contrast, Saccharomyces cerevisiae cells deleted for SGS1 grow with wild-type kinetics. To investigate the role of Sgs1p in DNA replication, we have monitored S phase progression in sgs1Δ cells. Unexpectedly, we find that these cells progress faster through S phase than their wild-type counterparts. Using bromodeoxyuridine incorporation and DNA combing, we show that replication forks are moving more rapidly in the absence of the Sgs1 helicase. However, completion of DNA replication is strongly retarded at the rDNA array of sgs1Δ cells, presumably because of their inability to prevent recombination at stalled forks, which are very abundant at this locus. These data suggest that Sgs1p is not required for processive DNA synthesis but prevents genomic instability by coordinating replication and recombination events during S phase.